The unknown Lenin : from the secret archive - Lenin, Vladimir Ilʹich, 1870-1924 (Annals of Communism., 1996)
Was Lenin a visionary whose ideals were subverted by his followers? Or was he a cynical misanthrope, even crueler than Stalin? This book, which contains newly released documents from the Lenin archive in Russia, lays bare Lenin the man and the politician, leaving little doubt that he was a ruthless and manipulative leader who used terror, subversion, and persecution to achieve his goals. Edited and introduced by the eminent scholar Richard Pipes, the documents date from 1886 through the end of Lenin's life. They reveal, among other things, that Lenin's purpose in invading Poland in 1920 was not merely to sovietize that country but to use it as a springboard for the invasion of Germany and England; Lenin took money from the Germans (here we have the first incontrovertible evidence for this); in 1919 Lenin issued instructions to the Communist authorities in the Ukraine not to accept Jews in the Soviet government of that republic; as late as 1922 Lenin believed in the imminence of social revolution in the West, and he planned subversion in Finland, Turkey, Lithuania, and other countries; Lenin had little regard for Trotsky's judgment on important matters and relied heavily on Stalin; Lenin assiduously tracked dissident intellectuals and urged repressive action or deportation; and Lenin launched a political offensive against the Orthodox Church, ordering that priests who resisted seizure of church property be shot - "the more the better."